Global Science Diplomacy in the Digital Age: Socio-economic and Legal Layout of International Scientific Cooperation - KOKENOV, Rashitdin S.; KAKENOVA, Galina M. (Journal of Advanced Research in Law and Economics; Vol 10 No 5 (2019): JARLE Volume X Issue 5(43) Fall 2019, 2019)
Conventional diplomacy has always relied on scientific expertise. Scientists, being ‘neutral’ representatives of their countries, are looking for answers to the global challenges of our time, common to all of humanity. As Anton Chekhov said: ‘There is no national science, just as there is no national multiplication table; what’s national is no longer a science’. Diplomats are people whose main task is to promote the interests and values of their country on the world stages; therefore, the purpose of this study is to analyze the development of scientific diplomacy in various countries. As a result of the study, the authors concluded that scientific diplomacy always reflects the interests of a state and therefore differs from international scientific cooperation. At the same time, there are many areas of common interest between science and diplomacy. Diplomats are interested in the key values of science – the universality and neutrality of knowledge, and they, in turn, can contribute to the activities of scientists. The authors conclude that there are many examples in history when scientific problems reached the level of diplomatic relations, and sometimes acted as their catalyst. On the contrary, diplomats often stimulated cooperation between countries in research, science, and technology. In this regard, Kazakhstan is interested in the best practices of developed countries in the field of scientific diplomacy.